1993
DOI: 10.1007/bf01316510
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical study of colonic cancer in experimental colitis of rats

Abstract: A reliable test for premalignant lesions in the development of colonic cancer in chronic ulcerative colitis has been needed. Thus, we designed this cytochemical study, using a model of experimental colitis and colonic tumors induced in Wistar male rats by the feeding of dextran sulfate sodium. The colitis had histologic similarities to ulcerative colitis in man. The percent frequency of polypoid lesions (dysplasia or dysplasia with carcinoma in situ) in the cecum and ascending colon was about 25% at three mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
27
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 26 publications
2
27
0
Order By: Relevance
“…13) Colorectal carcinomas developed in rats fed DSS for as long as 6 months. 14) Recently, Cooper et al 15) reported a relationship between the severity of DSS-induced inflammation and colorectal carcinogenesis which is similar to that of human UC-associated dysplasia and cancer regarding histopathology. However, these studies basically need a long experimental period or repeated administration of DSS.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…13) Colorectal carcinomas developed in rats fed DSS for as long as 6 months. 14) Recently, Cooper et al 15) reported a relationship between the severity of DSS-induced inflammation and colorectal carcinogenesis which is similar to that of human UC-associated dysplasia and cancer regarding histopathology. However, these studies basically need a long experimental period or repeated administration of DSS.…”
mentioning
confidence: 81%
“…However, these studies basically need a long experimental period or repeated administration of DSS. [14][15][16] In addition, our previous study demonstrated that treatment with the non-genotoxic carcinogen DSS enhances the development of putative precursor lesions (aberrant crypt foci) for colonic adenocarcinoma in rats. 17) In the first report of our experimental studies of inflammation-related carcinogenesis in mouse colon, we proposed a novel mouse model, using azoxymethane (AOM) and DSS.…”
mentioning
confidence: 94%
“…IBD can be experimentally induced by administering dextran sulfate sodium (DSS) orally in mice (11,32), rats (37), hamsters (40), or guinea pigs (21). DSS can produce both acute and chronic ulcerative colitis, with features somewhat similar to the symptomatic and histological findings for colitis in humans (11,32).…”
mentioning
confidence: 99%
“…The characteristics of various animal models of IBD have been extensively reviewed by Boismenu and Chen (23). The oral administration of dextran sulfate sodium (DSS) induces IBD in experimental animals including mice (24), hamsters (25), rats (26), and guinea pigs (27). Affected animals manifest weight loss, bloody diarrhea, and a hunched posture, and the histological phenotypes (24) are similar to those of human IBD.…”
mentioning
confidence: 99%